Effect of Soil-Type and Fines Content on Liquefaction Resistance—shear-Wave Velocity Correlation - Ecemiş, Nurhan; Ecemiş, Nurhan (Taylor & Francis, 2020)
Direct measurement of shear-wave velocity, Vs, in the field to evaluate the liquefaction resistance of soils is an alternative or complement approach to penetration-based methods. However, the existing liquefaction assessment methods established on the Vs have uncertainties about how the fines content and soil-type change the relationship between Vs and liquefaction resistance. The first part of this paper discusses the existence of fines on the correlation between cone penetration resistance and Vs. The second part focuses on the liquefaction resistance that is construed over again using the simplified cone penetration test (CPT)-based liquefaction screening procedure in terms of Vs for three distinct ranges of non-/low plastic fines content <35% fines. The outcomes of the investigation indicate that for each fines content, the correlation between CRR and Vs1 is not unique; there is a significant scattering of the curves for different soil types. Finally, using the results of this investigation as well as the simplified CPT-based liquefaction screening method, a soil-type specific CRR–Vs1 relationship developed for the unbounded, very young (Holocene-age) soils. © 2018 Taylor & Francis Group, LLC
Keywords: Cone penetration resistance; CPT-based soil type; Liquefaction resistance; Sand with fines; Shear-wave velocity